In-Fiber Graphene-hBN Polarizer With Enhanced Performance and Bandwidth - Xiaoying He; Anqi Hu; Xia Guo (IEEE Photonics Journal)
Graphene and hBN as two-dimensional materials with excellent optical properties can be combined with other materials. In this paper, graphene and hBN is sequentially deposited on the surface of the silicon-core fiber to serve as transverse magnetic (TM) or transverse electric (TE) mode polarizer alternatively depending on the input wavelength and the diameter of the silicon-core. The Gr/hBN stack structure on the surface silicon-core microfiber is used not only for enlarging the wavelength bandwidth, such as from 350 nm (TM) and 670 nm (TE) for double Gr/hBN stack to 300 nm (TM) and 550 nm (TE) for single Gr/hBN stack, but also enhancing the light-graphene interaction to multiply the polarization extinction ratio, as compared with that of monolayer graphene. Small radius silicon core could provide large light-graphene interaction for flat extinction ratio with different thickness of the hBN.